The hamster (mesocricetus auratus) as experimental model in chagas' disease: parasitological and histopathological studies in acute and chronic phases of Trypanosoma cruzi infection - Luis Eduardo Ramirez; Eliane Lages-Silva; José Maria Soares Junior; Edmundo Chapadeiro (Revista da Sociedade Brasileira de Medicina Tropical, 1994)
This research characterizes the acute and chronic phases of Chagas ' disease in hamster through parasitological and histopathological studies. The acute phase was achieved with 44 young hamsters injected intraperitoneally with 100.000 blood trypomastigotes of Benedito and Y strains of T. cruzi. The chronic phase was induced in 46 hamsters injected intraperitoneally with 35.000 trypomastigotes ofVicentina, Benedito and Y strains. Animals were sacrificed at regular intervals of 24 hours of acute phase and from the 3rd to the 10th month of infection ofchronic phase. In the acute phase, parasites were easily recoveredfrom all animals and there was an inflammatory reaction characterized by mononuclear and polymorphous leukocyte infiltration of variable degree in the majority of tissues and organs, specially in the connective loose and fatty tissues, smooth muscle myocardium and skeletal muscle. In the chronic phase the lesions occurred in the same tissues and organs, but the inflammatory response was less severe and characterized by mononuclear infiltration mainly with focal or zonalfibrosis in the myocardiun. In 50% of infected animals parasites were found inmyocardiun and recoveredfrom pericardic, peritoneal and ascitic fluids in some animals. Signs of heart failure, sudden death and enlargement of bowel were observed regularly. We concluded that the hamster is an useful model for Chagas' disease studies.